2020
DOI: 10.3390/jcm9082430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BRAF Mutation Screening Strategies in a Large Real-Life Series of Advanced Melanoma Patients

Abstract: Malignant melanoma (MM) is one of the deadliest skin cancers. BRAF mutation status plays a predominant role in the management of MM patients. The aim of this study was to compare BRAF mutational testing performed by conventional nucleotide sequencing approaches with either real-time polymerase chain reaction (rtPCR) or next-generation sequencing (NGS) assays in a real-life, hospital-based series of advanced MM patients. Consecutive patients with AJCC (American Joint Committee on Cancer) stage IIIC and IV MM fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The main findings of this study indicate that in the South Region of Portugal, the median age of diagnosis of cutaneous melanoma is 65 years and that 50% of all cases in the study period were diagnosed at ages between 52 and 75 years of age, in line with previously published data 17,18 . Moreover, it shows that more advanced age significantly increases the odds of recurrence, both at stages I-II and at stage III.…”
Section: Discussionsupporting
confidence: 90%
“…The main findings of this study indicate that in the South Region of Portugal, the median age of diagnosis of cutaneous melanoma is 65 years and that 50% of all cases in the study period were diagnosed at ages between 52 and 75 years of age, in line with previously published data 17,18 . Moreover, it shows that more advanced age significantly increases the odds of recurrence, both at stages I-II and at stage III.…”
Section: Discussionsupporting
confidence: 90%
“…The predominance of either GLI1 or GLI2 in relation to the development of BCC is still unclear; however, there seems to be a positive feedback loop in which GLI2 directly activates the expression of GLI1. Moreover, there is a small number of sporadic BCCs where SMO mutations are found, also resulting in the up-regulation of this pathway [42,[56][57][58][59][60][61].…”
Section: Gene Mutations In Nmscmentioning
confidence: 99%
“…In total, 16 studies [16,17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] have already reported a comparison between the Idylla method and other molecular reference methods for the assessment of the BRAF V600E mutation in melanoma patients at the time of the publication (Table 5). Most of them used the CE-IVD Idylla TM BRAF Mutation Test with a concordance rate ranging from 96.2% to 100% when compared with NGS, Sanger sequencing, pyrosequencing, or digital PCR, confirming that the test is reliable.…”
Section: Discussionmentioning
confidence: 99%